2009
DOI: 10.1101/gr.097212.109
|View full text |Cite
|
Sign up to set email alerts
|

An integrative genomic analysis identifies Bhmt2 as a diet-dependent genetic factor protecting against acetaminophen-induced liver toxicity

Abstract: Acetaminophen-induced liver toxicity is the most frequent precipitating cause of acute liver failure and liver transplant, but contemporary medical practice has mainly focused on patient management after a liver injury has been induced. An integrative genetic, transcriptional, and two-dimensional NMR-based metabolomic analysis performed using multiple inbred mouse strains, along with knowledge-based filtering of these data, identified betaine-homocysteine methyltransferase 2 (Bhmt2) as a diet-dependent genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…In this study, hepatic expression of the following genes were determined after APAP administration: NF-E2-related factor-2 (Nrf2), heme oxygenase-1 (HO-1), heat shock protein 70 (Hsp70), insulin-like growth factor binding protein-1 (IGFBP-1), ␥-glutamylcysteine synthetase (␥GCS), Tribbles homolog 3 (Trib3), glutathione transferases (GSTs) -1 (GSTP1) and GST (GSTK), peroxisome proliferator-activated receptor-␣ (PPAR␣), L-carnitine palmitoyltransferase 1 (L-CPT1), acylcoenzyme A oxidase (ACO), and pyruvate dehydrogenase kinase 4 (PDK4). Recent investigations showed that increased Trib3 expression was a good marker to detect GSH depletion secondary to its conjugation (Gao et al, 2010), and high basal PDK4 expression could increase sensitivity to APAP-induced hepatotoxicity (Liu et al, 2010). As shown in Fig.…”
Section: Preliminary Investigations In Lean and Obese Micementioning
confidence: 98%
“…In this study, hepatic expression of the following genes were determined after APAP administration: NF-E2-related factor-2 (Nrf2), heme oxygenase-1 (HO-1), heat shock protein 70 (Hsp70), insulin-like growth factor binding protein-1 (IGFBP-1), ␥-glutamylcysteine synthetase (␥GCS), Tribbles homolog 3 (Trib3), glutathione transferases (GSTs) -1 (GSTP1) and GST (GSTK), peroxisome proliferator-activated receptor-␣ (PPAR␣), L-carnitine palmitoyltransferase 1 (L-CPT1), acylcoenzyme A oxidase (ACO), and pyruvate dehydrogenase kinase 4 (PDK4). Recent investigations showed that increased Trib3 expression was a good marker to detect GSH depletion secondary to its conjugation (Gao et al, 2010), and high basal PDK4 expression could increase sensitivity to APAP-induced hepatotoxicity (Liu et al, 2010). As shown in Fig.…”
Section: Preliminary Investigations In Lean and Obese Micementioning
confidence: 98%
“…In fact, analysis of mouse genetic models has generated novel approaches for treatment of narcotic drug addiction (20) and for prevention of acetaminophen-induced liver toxicity (21). Differences in response to RSV have been observed among inbred mouse strains, including differences in viral load (22)(23)(24) postinfection, and in eosinophilic responses after vaccination with the RSV glycoprotein (25,26).…”
Section: R Espiratory Syncytial Virus (Rsv) Is the Most Significant Cmentioning
confidence: 99%
“…We also evaluated a common nonsynonymous polymorphism in the human CD44 gene (I479T) that was associated with increased serum liver injury biomarker levels in healthy volunteers who chronically consumed acetaminophen (Watkins et al, 2006;Harrill et al, 2009), and also a common nonsynonymous polymorphism in the human betaine-homocysteine methyltransferase 1 (BHMT1) gene (R239Q) because the closely related murine Bhmt2 gene was previously identified as protective against acetaminopheninduced hepatotoxicity in a mouse genomics study (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%